2016
DOI: 10.1002/ptr.5726
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory Effects of Functionally Active Compounds Isolated from Aged Black Garlic

Abstract: The antiinflammatory effects of functionally active compounds isolated from aged black garlic (AGE-1 and AGE-2) were investigated using a lipopolysaccharide-induced inflammatory response model. To examine the potential antiinflammatory properties of AGE-1 and AGE-2, cell viability as well as nitric oxide, prostaglandin E2, and pro-inflammatory cytokine [interleukin-6 (IL-6), TNF-α, and IL-1β] levels were measured. The mRNA and protein expression levels of inducible nitric oxide synthase and cyclooxygenase-2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 37 publications
1
35
1
Order By: Relevance
“…Conversely, the obtained results indicated that A. sativum and A. Iranicum, especially at higher concentrations, significantly increased macrophage viability indices, and A. asarense decreased the indices. Kim et al (2017) claimed that after the treatment of RAW 264.7 cells with black A. sativum bulb-derived components, their cell viabilities did not significantly change [24]. A 14 kD protein derived A. sativum bulb had no impact on J774A.1 macrophage viability at 5-30 µg/mL [25].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the obtained results indicated that A. sativum and A. Iranicum, especially at higher concentrations, significantly increased macrophage viability indices, and A. asarense decreased the indices. Kim et al (2017) claimed that after the treatment of RAW 264.7 cells with black A. sativum bulb-derived components, their cell viabilities did not significantly change [24]. A 14 kD protein derived A. sativum bulb had no impact on J774A.1 macrophage viability at 5-30 µg/mL [25].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to studies regarding antioxidant activity of ABG, a relatively small number of studies have considered the anti-inflammatory activity of ABG. Some compounds showing anti-inflammatory effects in ABG are identified as pyruvate, 2-linoleoylglycerol, and 5-hydroxymethylfurfural [ 9 , 18 , 19 ]. Pyruvate has anti-inflammatory activity as well as antioxidant activity [ 47 , 48 ].…”
Section: Properties Of Abgmentioning
confidence: 99%
“…Pyruvate reduces lipopolysaccharide (LPS)-induced nitric oxide (NO), and prostaglandin E 2 (PGE 2 ) is released [ 9 ]. The 2-linoleoylglycerol isolated from ABG suppresses the levels of NO, PGE 2 , and pro-inflammatory cytokines via inhibition of mitogen activated protein kinases signaling pathways in LPS-induced RAW264.7 cells [ 19 ]. The 5-hydroxymethylfurfural reduces TNF-α-induced monocytic cell adhesion to human umbilical vein endothelial cells (HUVECs) through suppression of vascular cell adhesion molecule-1 (VCAM-1) expression, ROS generation, and nuclear factor kappa B (NF-κB) activation [ 18 ].…”
Section: Properties Of Abgmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that black garlic has a variety of physiological functions, such as anti-inflammatory, cardioprotective, and antioxidant effects. [6][7][8][9] Jeong et al found that the 2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonate) (ABTS) radical scavenging activity and the 2.2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity of black garlic water extract were 2.0 times and 3.5 times those of fresh garlic water extract, respectively. 8 During the processing of black garlic, obvious sensory changes occur.…”
Section: Introductionmentioning
confidence: 99%